Training Egyptian undergraduate mathematics students to implement REACT strategies: An approach to strengthen their conceptual and procedural knowledge of rational numbers and capability to create contextual situations - Elbehary, Samah Gamal Ahmed (Al-Jabar: Jurnal Pendidikan Matematika, 2024)
Background: The quality of instruction significantly influences students' understanding of school mathematics, highlighting the importance of initial teacher education. Concerns about how to enhance prospective teachers' pedagogical skills remain significant. This study addresses the scarcity of national investigations on employing REACT strategies in preparing pre-service mathematics teachers.Aim: This study aims to strengthen the conceptual and procedural knowledge of rational numbers among undergraduate mathematics students and develop their abilities to create contextual situations that align with the five interpretations of rational numbers: part-whole, operator, quotient, ratio, and measure.Method: An embedded design was employed, selecting a convenient sample of thirty undergraduates from the mathematics teacher preparation program at the Faculty of Education, Tanta University in Egypt, during the academic year 2022-2023. Data collection involved administering a test to assess participants' conceptual and procedural knowledge and a survey to explore their capabilities in creating contextual situations. The data were analyzed using descriptive and inferential statistics, coupled with qualitative analysis of participants' answers.Results: The adapted training significantly enhanced participants' knowledge of rational numbers, evidenced by a large effect size (Cohen’s d = 2.71). Furthermore, participants' ability to generate contextual scenarios improved, demonstrated by the diversity of contexts and the inclusion of all interpretations of rational numbers in their scenarios.Conclusion: The study demonstrates the effectiveness of REACT strategies in improving prospective mathematics teachers' knowledge and skills. Future research should evaluate the quality of contextual scenarios proposed by prospective teachers across various domains of mathematics.